Implementation of Da’wah in Counteracting Hoax News on Social Media - Husniya, Eta Amala; Auliya, Mikhlathul; Nafisah, Iklil (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
The primary objective of this study is to examine the significance of da'wah values within the MAFINDO (Masyarakat Anti Fitnah Indonesia) website as a means to combat hoax news on social media. The research methodology employed is content analysis, which helps reveal the contents of the research instrument. The study utilizes the Media Dependency Theory to evaluate MAFINDO's image as portrayed in several of its posts. In this particular case, the Media Dependency Theory serves as a tool to better understand how da'wah values manifest in the content presented on the MAFINDO website, aiming to counter hoax news on social media. The study's findings indicate the presence of two da'wah values on the website. Firstly, the MAFINDO website serves as a platform for truth, promoting the value of information disclosure. Additionally, the value of da'wah is evident in the "fact-checking" tool, which makes a significant contribution to fostering an intelligent, critical, and honorable society. Individuals can establish trust and uphold national and societal harmony by collaborating to prevent the spread of fake news. Previous literature lacks research examining the role of da'wah in countering hoaxes, making this study a valuable contribution to the social and religious communication field and the study of hoax news on social media. This research highlights the correlation between social and religious factors in MAFINDO's role as an institution combating defamation and slander, particularly in anti-corruption efforts.